Penyelesaian Sengketa dalam Perjanjian Pembiayaan Konsumen sebagai Akibat Wanprestasi - Meita Djohan Oelangan (Law Faculty of Universitas Bandar Lampung, 2012)
Defrayal agreement represent one of the way of to get required goods where buyer unable to pay for goods price cashly. Agreement like this non meaning do not contain risk. Risk will emerge if consumer do wanprestasi. Problem of research is how solving of dispute between the parties as effect of existence of wanprestasi. Strive the Solving of in the event of dispute because effect of wanprestasi use systems